Women's rights to succession in unregistered marriages: a reference to the instrument of wasiyyah - Halim, Akmal Hidayah; Abdullah, Mohamad Asmadi (International Islamic University Malaysia, 2008)
It is an essential requirement for a marriage to be registered according to the procedures as provided by the law. Non-registration of a marriage leads to the non-availability of a marriage certificate, being the main proof of the existence of the marital relationship. This situation results in various legal complications in claiming the rights, including a right to property under the law of succession which arises upon the death of the spouse. Such a right, even though guaranteed by the Syarīcah, is not recognized by Malaysian law. This article seeks to examine the women’s rights to succession in cases of unregistered marriage with special reference to the execution of a waṣiyyah as a useful instrument to protect the rights of the unregistered wives against husbands’ estates.